What It Means to "Win" in Small College Athletics: Strategic Contingency Theory and Alternative Success - Claire C. Zvosec; Jordan R. Bass (University of Kansas Libraries, 2022)
The purpose of this study was to gain a deep understanding of how athletics success is defined and operationalized for small colleges in Division III athletics. Strategic Contingency Theory was utilized as a framework to examine and better understand how the small college athletics department operates "successfully." The underlying premise of Strategic Contingency Theory is that an organization must adapt in order to survive. In-depth interviews were conducted with NCAA Division III Athletics Directors, campus administrators (e.g., President, Provost, Vice President for Enrollment Management), and Faculty Athletics Representatives to better understand how university and athletics administrators define athletics program success at small colleges. In all, 33 interviews were conducted across seven states at 11 different Division III institutions where student-athletes comprise 20% or more of the student body.